2021
DOI: 10.3934/dcdss.2020399
|View full text |Cite
|
Sign up to set email alerts
|

Darcy-Forchheimer relation in Magnetohydrodynamic Jeffrey nanofluid flow over stretching surface

Abstract: Present article aims to investigate the heat and mass transfer developments in boundary layer Jeffery nanofluid flow via Darcy-Forchheimer relation over a stretching surface. A viscous Jeffery naonfluid saturates the porous medium under Darcy-Forchheimer relation. A variable magnetic effect normal to the flow direction is applied to reinforce the electro-magnetic conductivity of the nanofluid. However, small magnetic Reynolds is considered to dismiss the induced magnetic influence. The so-formulated set of gov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 46 publications
(45 reference statements)
0
29
0
Order By: Relevance
“…In the literature mentioned above, the studies have been mainly reported on stretching surfaces with various assumptions including the porosity factor, Brownian diffusion and thermophoresis using HAM [25][26][27][28][29][30][31]. However, no research is found emphasizing the role of stagnation point in third grade fluid towards stretching surface (cylinder) which affirms the novelty of the present problem.…”
Section: Introductionmentioning
confidence: 55%
“…In the literature mentioned above, the studies have been mainly reported on stretching surfaces with various assumptions including the porosity factor, Brownian diffusion and thermophoresis using HAM [25][26][27][28][29][30][31]. However, no research is found emphasizing the role of stagnation point in third grade fluid towards stretching surface (cylinder) which affirms the novelty of the present problem.…”
Section: Introductionmentioning
confidence: 55%
“…(c) Unlike the numerical packages, the HAM gives convergent results on the basis of initial guesses. For more details on HAM, one can see and cross‐references cited therein. The method requires an assumption of suitable initial guesses that satisfy the boundary conditions.…”
Section: Solution Methodologymentioning
confidence: 99%
“…Akbar [9] investigated the bio-convection peristaltic convection of nanofluid in a given asymmetric channel saturated with gyrotactic micro-organisms. Mabood et al [10] reported a free convective flow of non-Newtonian-type nanofluids (see for example [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] to understand the term non-Newtonian nanofluids) in permeable medium saturated with gyrotactic-type micro-organisms.…”
Section: Introductionmentioning
confidence: 99%